Analisis Fenomena Drifting Liar dalam Perspektif Asosiasi Diferensial: Studi Kasus di Pondok Indah - Yusuf Mujaddid; Lucky Nurhadiyanto (LPPM Universitas Ekasakti Padang, 2024)
: Street drifting is a phenomenon in which drivers perform high-risk manoeuvres on public roads without permission, has become an increasingly acute social and security issue. In Indonesia, the legality of this activity refers to compliance with the regulations of the applicable laws. Drifting permitted on the circuit under the provisions of the Indonesian Motor Union (IMI), however, often develops in an illegal context. The research uses a qualitative approach to explore the phenomenon of wild drifting in the Indah Pondok area, South Jakarta. Data collection methods involve field observations, interviews with two active perpetrators drifting wild in the area, and literature studies. The data obtained was then analyzed using the differential association theory by Edwin Sutherland (1939). The results of the analysis show that the motivation to engage in wild drifting is heavily influenced by social interaction, intimate groups, attitudes to the law, and physical conditions of the location. Wild drifters greatly appreciate the sensation of adrenaline, freedom, and flexibility offered by this activity.